ANTICONVULSANT ACTIVITY OF ANACARDIUM OCCIDENTALE L. LEAVES EXTRACT IN EXPERIMENTAL MICE - PANJWANI, DHARAMVEER; PUROHIT, VIMLA; SIDDIQUI, H.H. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study was undertaken to investigate the antidepressant-like effects of Anacardium occidentale (AO) L. leaves in the mouse forced swim test (FST) and tail suspension tests (TST). Materials and Methods: Swiss albino male mice were used for the study. Acute toxicity and neurotoxicity studies were performed. In the acute study, the ethanolic extract at a dose of 200 and 400 mg/kg were administered in single dose 1 hr prior to the test. In the chronic study, extracts were administered once a day for a period of 14 days. Imipramine (10 mg/kg) and fluoxetine (10 mg/kg) were used as standard antidepressant agents throughout the study. The extract did not show any type of toxicity. Results: The results showed that the ethanolic extract decreased immobility periods significantly in a dose-dependent manner in both TST and FST. The observed results were also comparable with known standard drugs. The flavonoids apigenin and quercetin act as reversible monoamine oxidase inhibitors and selectively binds with high affinity to the central benzodiazepine receptors possesses important antidepressant activity. The literature reveals that the main constituents of AO are flavonoids, quercetin, apigenin, tannins, and alkaloids. Conclusion: It was possible that the extract exerted the antidepressant activity through interaction with adrenergic, dopaminergic, serotonergic and gamma-aminobutyric acid-anergic system. Keywords: Anacardium occidentale, Strychnine, Seizure, Neurotoxicity.